Design and Implementation of Proportional-Integral Controller for Single Phase Stand-Alone Inverter with an LC-Filter - Kareem, Tamarah; Shneen, Salam Waley; Al-Abbasi, Mohammed (International Journal of Robotics and Control Systems, 2025)
Obtaining a sine wave from a DC source using an inverter and a filter is a challenge that requires a suitable design to meet load requirements as operating conditions change. This work aims to develop a suitable design for an LC-type pass-through filter and a suitable design for a conventional controller. A simulation model for the implementation and operation of a single-phase standalone inverter is being developed and designed using Matlab. In this work, the researchers demonstrate the behavior of a simulated system using a single-phase inverter model connected to a 400 V DC power supply. An LC-type filter is also connected to the inverter and the load. Tests are conducted to determine the system's behavior under various conditions. The researchers are interested in changing operating conditions, and the problem of load variations, on the one hand, and transients and the system's return to a steady state, on the other. The researchers propose one method for overcoming system fluctuations using a conventional controller (PI controller). Tests can cover identifying system behavior, and from there, using the controller, an appropriate reference voltage can be set to supply the load. The proposed model consists of a power supply, four IGBT transistor switches to build a single-phase bridge inverter, a filter with an inductor (4.06e-3H) and a capacitor (6.23e-6F), as well as a reference voltage of 200V and 300V, and a load of 55? and 100?. A suitable conventional microcontroller (PIC) is also designed. The feasibility of providing a sine wave with the proposed reference voltage has been verified, proving the feasibility of the model and its potential for future use. Matlab was used to conduct simulation tests of the proposed model, and high performance, accuracy, and quality were obtained at a level suitable for real-time applications.